Mô hình thực nghiệm phản ứng bề mặt trong thiết bị Aerosol của quá trình tổng hợp vật liệu nano tinh thể TiO2 - Thắng, Cao Xuân; Thiêm, Phạm Văn; Xá, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
Nanometer-sized titania particles were prepared by low thermal of  vapor hydrolysis process titanium tetrachloride (TiCl4) in a furnace type aerosol reactor. Reaction model was introduced because simple reaction coagulation (SRC) model, which is valid at high conversion, was found to be improper at high concentration and low conversion. The size of titania particles increased from 10 to 50 nm with increasing input concentration of TiCl4 from 3.06×10-7 to 1.59×10-6 mol/ml and the residence times from 7 s to 35 s at 250 oC. The reaction model predicted the decreasing trend of the particle size with increasing temperature, whereas the SRC model simulation predicted that the size was an increasing function of the temperature. Keywords: Nano TiO2, aerosol reactor, vapor hydrolysis.